Physical condition and root development of grasses in a constructed minesoil after coal mining - Stumpf, Lizete; Pauletto, Eloy Antonio; Spinelli Pinto, Luiz Fernando; Garcia, Gabriel Furtado; Ambus, Jordano Vaz; Silva, Tiago Stumpf da; Pinto, Marilia Alves Brito; Tuchtenhagen, Ivana Kruger (Pesquisa Agropecuaria Brasileira, 2016)
The objective of this work was to evaluate the root development of the physical condition and the potential of agricultural use of a constructed minesoil after coal mining, besides the root development of tropical grasses in this soil, considering different revegetation periods. The soil was constructed in early 2003, and the experiment was installed in November/December 2007. Soil physical condition was evaluated in plots vegetated with perennial grasses such as Urochloa humidicola, Panicum maximum, and U. brizantha. In July 2012, disturbed and undisturbed soil samples were taken for determining physical and chemical attributes in the 0.00–0.10, 0.10–0.20, and 0.20–0.30-m soil layers. Soil monoliths were collected for characterizing the root system. After 58 months of revegetation, the physical condition of the constructed minesoil is still inadequate to an agricultural use that requires intensive soil management. Among the evaluated layers, only the 0.00–0.10-m layer provides conditions for the soil to function properly in the ecosystem. Urochloa brizantha was more promising for the recovery of soil structure in the 0.00–0.10-m soil layer, and root density was the most sensitive attribute to distinguish the potential development of the different species in this layer.